2015
DOI: 10.1080/15384101.2015.1041694
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen withdrawal, increased breast cancer risk and the KRAS-variant

Abstract: Keywords: breast cancer risk, estrogen withdrawal, KRAS-variant, multiple primary breast cancer, triple negative breast cancer, tumor biologyThe KRAS-variant is a biologically functional, microRNA binding site variant, which predicts increased cancer risk especially for women. Because external exposures, such as chemotherapy, differentially impact the effect of this mutation, we evaluated the association of estrogen exposures, breast cancer (BC) risk and tumor biology in women with the KRAS-variant. Women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 39 publications
3
12
0
Order By: Relevance
“…This gene mainly functions in signaling pathways involving membrane receptors and cAMP. KRAS has the strongest influence on malignant cancer in the RAS family (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This gene mainly functions in signaling pathways involving membrane receptors and cAMP. KRAS has the strongest influence on malignant cancer in the RAS family (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study from Ovarian Cancer Association Consortium and colleagues with performed rs61764370 genotyping for 140,012 women the authors reported no association of rs61764370 with risk of ovarian or breast cancer nor with clinical outcome [5]. Whereas McVeigh and colleagues described the KRAS variant as significant marker, which in combination with estrogen withdrawal increases breast cancer risk and predicts aggressive tumor biology [6].…”
Section: S I N G L E N U C L E O T I D E P O L Y M O R P H I S M Rs61mentioning
confidence: 99%
“…5 This combination of clinical observations led McVeigh and colleagues to investigate how estrogen might impact breast cancer risk and tumor biology for individuals with the KRAS-variant allele. 6 In their study, 1712…”
mentioning
confidence: 92%